2013
DOI: 10.1109/jlt.2013.2242429
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modulus Blind Equalizations for Coherent Quadrature Duobinary Spectrum Shaped PM-QPSK Digital Signal Processing

Abstract: A novel digital signal processing (DSP) scheme for quadrature duobinary (QDB) spectrum shaped polarization multiplexed quadrature phase shift keying (PM-QPSK) based on multi-modulus blind equalizations (MMBE) is proposed and demonstrated with both simulation and experimental results. The key algorithms for this novel digital signal processing scheme include the cascaded multi-modulus algorithm (CMMA) for blind polarization de-multiplexing, multi-modulus QPSK partitioning frequency offset estimation (FOE) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 13 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…In the underwater communication, the envelope of the transmit signal is always changeless such as PSK. CMA is based on the characteristic and is very suitable for the equalization of this kind of signal (Zhang, Yu and Chi, 2013;Li, 2015;Zhang, Chen and Hanzo, 2014). In the coherent underwater acoustic communication, the transmitting signal waveform has constant envelope, such as PSK (phase-shift keying) signal.…”
Section: The Constant Modulus Algorithmmentioning
confidence: 99%
“…In the underwater communication, the envelope of the transmit signal is always changeless such as PSK. CMA is based on the characteristic and is very suitable for the equalization of this kind of signal (Zhang, Yu and Chi, 2013;Li, 2015;Zhang, Chen and Hanzo, 2014). In the coherent underwater acoustic communication, the transmitting signal waveform has constant envelope, such as PSK (phase-shift keying) signal.…”
Section: The Constant Modulus Algorithmmentioning
confidence: 99%
“…For the phase recovery, Viterbi algorithm is utilized to cancel the phase noise of QPSK signal after 4-point FFT. For the CMMA algorithm, we only select the inner three rings/radii for the error signal calculation to increase equalizer robustness [10,11], which is the same as CMMA algorithm for 9-QAM signal [12,13]. We also analyze the PAPR of Quad-Carrier QPSK-OFDM signal and traditional QPSK-OFDM signal.…”
Section: Principlementioning
confidence: 99%
“…At receiver, after optical to electrical (O/E) conversion, a digital filter is used to separate the 4-subcarrier, and then DSP is applied for each subcarrier [9]. 4-subcarrier OFDM signal shows as a 25-QAM signal in the time domain, and it can be blindly equalized with cascaded multi-modulus algorithm (CMMA) equalization in the time domain [10][11][12][13]. With the blind equalization, channel estimation and equalization, FOE, and phase recovery can be implemented without TS and pilot tones.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [13], 40 Gbit/s QPSK signal polarization multiplexing transmission was used in single-mode fiber (SMF) for 100 km, signals received are processed via A/D conversion offline DSP. In 2008, the Nortel research team reported a coherent optical communication experiment, which is a milestone.…”
Section: Introductionmentioning
confidence: 99%